ADSORPSI DAN DESORPSI Cr(VI) PADA ADSORBEN BATU CADAS KARANGASEM HASIL LIMBAH KERAJINAN CANDI BALI TERAKTIVASI NaOH DAN TERSALUT Fe(OH)3 - I Made Dupi Andika; I Nengah Simpen; Ketut Gede Dharma Putra (Jurnal Kimia (Journal of Chemistry), 2016)
This research discusses the adsorption-desorption of Cr(VI) by the adsorbent made from Karangasem cadas rock which is the waste of Balinese temple production. The adsorbent was activated with  NaOH and coated with Fe(OH)3. The aim of the study was to investigate the capability of cadas rock in Cr6+ adsorption. The rock was activated with various concentrations of NaOH followed by coating process with Fe(OH)3. Each adsorbent was characterized for its specific surface area and surface acidity. The equilibrium time, adsorption isotherms and adsorption capacity were also investigated. The adsorbent with the highest adsorption capacity was then desorbed using HNO3 2 mol/L, NaOH 1 mol/L, and saturated NH4Cl. The result suggested that the highest surface acidity was showed by the control adsorbent which was 0.2836 ± 0.0106 mmol/g with an acid site of 1.7079 x 1020 atoms/g. The highest spesific surface area was showed by the adsorbent activated with 6M NaOH  and coated with Fe(OH)3, which was 34.5042 m2/g. The highest adsorption capacity was showed by the same adsorbent, which was 2.5253 mg/g with interaction time of 15 minutes at pH 5. This met the pattern of Langmuir adsorption isotherm. HNO3 was the most effective desorption substance resulted in a percentage of Cr desorbed of 2,15%.